2003
DOI: 10.1007/s00122-003-1293-1
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive segregation of erucic acid content in Brassica carinata A. Braun

Abstract: Two Ethiopian mustard ( Brassica carinata A. Braun) lines with low (about 10%) and zero erucic acid (C22:1) have been obtained. The low C22:1 mutant line L-2890 was isolated after a chemical-mutagen treatment of C-101 seeds (about 40% C22:1). The zero C22:1 line L-25X-1 was obtained by interspecific crossing. Our objective was to determine the genetic control of low and zero C22:1 contents in these lines and the relationship between the loci controlling these traits. Reciprocal crosses between L-2890, L-25X-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…In the six F 2 populations analysed, three from each reciprocal cross, the distribution of C22:1 content fitted a ratio of 1:15 (χ 2 =0·41, P =0·52) for the low:intermediate-high classes, respectively (Table 4). This segregation suggests the presence of two independent loci, which is in agreement with the model proposed ( M1 and M2 loci) for the inheritance of C22:1 in the mutant L-2890 (Del Río et al 2003).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In the six F 2 populations analysed, three from each reciprocal cross, the distribution of C22:1 content fitted a ratio of 1:15 (χ 2 =0·41, P =0·52) for the low:intermediate-high classes, respectively (Table 4). This segregation suggests the presence of two independent loci, which is in agreement with the model proposed ( M1 and M2 loci) for the inheritance of C22:1 in the mutant L-2890 (Del Río et al 2003).…”
Section: Resultssupporting
confidence: 90%
“…The fatty acid composition of the seed oil of mutant line L-2890, standard line C-101, and their reciprocal F 1 s, all grown in the same environment, is presented in Table 1. The inheritance of low C22:1 content in the mutant L-2890 was reported in a previous study and it was concluded that this trait was controlled by two loci ( M1 and M2 ) with partially recessive alleles m 1 and m 2 (Del Río et al 2003; Del Río-Celestino et al . 2005).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…To achieve this, induced mutations and hybridization can play a vital role. The use of mutagenesis permitted the development of Ethiopian mustard lines with specific fatty acid profiles such as lines with a high oleic acid content and some lines with a low C18:1 content (Velasco et al 1997) and also lines with low and high C22:1 contents whose genetics have been reported in previous studies (Velasco et al 1997, 1998; De Haro et al 2001; Del Rio et al 2003;). These oils with specific fatty acid profiles are in demand because of their improved nutritional and/or technological properties (Kinney 1994).…”
mentioning
confidence: 99%